CD73's Potential as an Immunotherapy Target in Gastrointestinal Cancers - Harvey, Jerry B.; Phan, Luan H.; Villarreal, Oscar E.; Bowser, Jessica L. (Frontiers in Immunology, 2020)
CD73, a cell surface 5’nucleotidase that generates adenosine, has emerged as an attractive therapeutic target for reprogramming cancer cells and the tumor microenvironment to dampen antitumor immune cell evasion. Decades of studies have paved the way for these findings, starting with the discovery of adenosine signaling, particularly adenosine A2A receptor (A2AR) signaling, as a potent suppressor of tissue-devastating immune cell responses and evolving with studies focusing on CD73 in breast cancer, melanoma, and non-small cell lung cancer. Gastrointestinal (GI) cancers are a major cause of cancer-related deaths. Evidence is mounting that shows promise for improving patient outcomes through incorporation of immunomodulatory strategies as monotherapy or in combination with current treatment options. Recently, several immune checkpoint inhibitors received FDA approval for use in GI cancers; however, clinical benefit is limited to only a few patients. Investigating molecular mechanisms promoting immunosuppression, such as CD73, in GI cancers can aid to current efforts to extend the efficacy of immunotherapy to more patients. In this review, we discuss current clinical and basic research studies on CD73 in GI cancers, including gastric, liver, pancreatic, and colorectal cancer, with special focus on the potential of CD73 as an immunotherapy target in these cancers. We also present a summary of current early phase clinical studies targeting CD73 and combination of these therapies with immune checkpoint inhibitors.